The Self-confidence of Sepak takraw athletes in selected public and private secondary schools in bulacan - Gerona, Edgar (Manila : National University, 2005)
The following statements disclose the researcher's rationale for conducting the present study. This study was deemed significant to the following people: school principals, sports coordinator, Trainers and coaches, parents, and most of all to the athletes themselves. For the school principals, it will help them understand the nature of the athletes and through it they will be able to design a well balance school and sports program that will enhance the students' abilities and skills. On the part of the trainers and coaches' knowing the athletes' strength and weaknesses will help them reinforced the athletes' capabilities and through it they will become more effective educational managers. It will also help them gain more objective insights into their styles of physical education management and thus have better understanding of some of the factors that influenced them. Likewise, the findings will then serve as a guide for the athletes to know themselves more fully and in order for them to develop a sense of self confidence most primarily in their dealings with their opponents, classmates, parents, teachers, and the people they work with.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.